Red and White Galangal Puree Antioxidant Activity and Phytochemistry Screening - Mardhiyyah, Kana; Yunita Intan Ryandini; Yopi Hermawan (Tropical Biopharmaca Research Center, IPB University, 2021)
Antioxidant prevents oxidative stress. One of the antioxidant sources is plant. Red and white galangal are herbal plants that are easy to grow and they may have antioxidant activity. The aim of this study was to compare antioxidant activity and phytochemistry screening of red galangal (Alpinia purpurata (Vieill.) K. Schum) and white galangal (Alpinia galanga (L.) Willd.). The method of this study used was the DPPH method and qualitative analysis. The results of this study showed that the value of antioxidant activity of red galangal was significantly higher than white galangal (p<0.05). The results of phytochemistry screening showed that red galangal contained alkaloids, flavonoids, phenolics, tannins, saponins, and triterpenoids. While white galangal contained alkaloids, flavonoids, phenolics, tannins, and triterpenoids. It is can be concluded that red galangal is more effective than white galangal.